(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Over the years, water pollution due primarily to the discharge of toxic heavy metals from industrial activities has served as a major challenge in the quest to provide a safe environment. Key among the technologies used for the treatment of wastewater contaminated with heavy metals is adsorption. In this study, mixed rice husk and cassava peel powder were used to develop microporous adsorbent with chemical modification by Sulphuric acid (H2SO4) for the batch adsorption of hexavalent chromium [Cr (VI)], Nickel(Ni), and Lead(Pb). Using adsorption equilibrium isotherms and adsorption kinetic study, a positive correlations (better fit) was obtained for Redlich-Peterson isotherm and Pseudo second order kinetic models. A maximum adsorption capacity of 139.18 mg/g, 3.66mg/g, and 5.58mg/g and a maximium removal of 93.60%, 98.20% and 93.80% were obtained for Chromium, Nickel, and Lead respectively. Therefore, rice husk and cassava peel usage were found to has a high chance of reducing solid waste management problems as well as having the potential to be effective in the removal of heavy metals from industrial effluents.